2014
DOI: 10.1111/cch.12201
|View full text |Cite
|
Sign up to set email alerts
|

Support and monitoring of families after child abuse detection based on parental characteristics at the Emergency Department

Abstract: Before referral by the ED two thirds of these families were already known to organizations. Monitoring may help provide a better, more sustained service and prevent and resolve domestic problems. A national database could help to link data and to streamline care for victims and families. We recommend a Randomized Controlled Trial to test the effectiveness of this Protocol in combination with the outcomes of the provided family support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
(9 reference statements)
1
6
0
Order By: Relevance
“…We found no statistically significant differences in levels of post-traumatic stress, anxiety and depression, behavioural problems and health-related quality of life between these children and community reference samples. A recent study of Child Abuse Counseling and Reporting Centre records of the Hague protocol (in which children were identified in the same manner as in our study) found low numbers of children needing support as well (Diderich et al 2015a). However, compared with previous studies, in which high levels of maltreatment and psychosocial impairment were found in children whose parents had similar problems (Diderich et al 2013;Hoytema van Konijnenburg et al 2013;Evans et al 2008;Wood & Sommers 2011;Ammerman et al 2010;Hser et al 2014;Torvik et al 2011), our findings are unexpected.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…We found no statistically significant differences in levels of post-traumatic stress, anxiety and depression, behavioural problems and health-related quality of life between these children and community reference samples. A recent study of Child Abuse Counseling and Reporting Centre records of the Hague protocol (in which children were identified in the same manner as in our study) found low numbers of children needing support as well (Diderich et al 2015a). However, compared with previous studies, in which high levels of maltreatment and psychosocial impairment were found in children whose parents had similar problems (Diderich et al 2013;Hoytema van Konijnenburg et al 2013;Evans et al 2008;Wood & Sommers 2011;Ammerman et al 2010;Hser et al 2014;Torvik et al 2011), our findings are unexpected.…”
Section: Discussionsupporting
confidence: 68%
“…Both in this study and in an evaluation of the Hague protocol using records to identify children in need of psychosocial support (Diderich et al 2015a), despite methodological limitations that might underestimate some of the symptoms, children identified because their parents visited the emergency department due to serious social problems seem fairly resilient to their parents' problems in the short term and do not experience more psychosocial symptoms than community children. Since the majority of these children are not in current need of specialized treatment, these findings support that it may not be necessary to evaluate all children at a specialized child maltreatment centre at this point.…”
Section: Clinical Impactmentioning
confidence: 91%
“…One had witnessed domestic violence. Four had experienced combinations of these types of maltreatment and referral was not substantiated in two cases [ 92 ].…”
Section: Resultsmentioning
confidence: 99%
“…Whether or not national protocols improve the reporting process for MRs or help to improve child outcomes would need to be tested. 82–84 …”
Section: Discussionmentioning
confidence: 99%